Harnessing Reciprocity to Promote Cooperation and the Provisioning of Public Goods. (October 2014) - Rand, David G.; Yoeli, Erez; Hoffman, Moshe
How can we maximize the common good? This is a central organizing question of public policy design, across political parties and ideologies. The answer typically involves the provisioning of public goods such as fresh air, national defense, and knowledge. Public goods are costly to produce but benefit everyone, thus creating a social dilemma: Individual and collective interests are in tension. Although individuals may want a public good to be produced, they typically would prefer not to be the ones who have to pay for it. Understanding how to motivate individuals to pay these costs is therefore of great importance for policy makers. Research provides advice on how to promote this type of "cooperative" behavior. Synthesizing a large body of research demonstrates the power of "reciprocity" for inducing cooperation: When others know that you have helped them, or acted to benefit the greater good, they are often more likely to reciprocate and help you in turn. Several conclusions stem from this line of thinking: People will be more likely to do their part when their actions are observable by others; people will pay more attention to how effective those actions are when efficacy is also observable; people will try to avoid situations where they could help, but often will help if asked directly; people are more likely to cooperate if they think others are also cooperating; and people can develop habits of cooperation that shape their default inclinations.